“Zonificación agroecológica del cultivo de maíz (zea mays) y su adaptabilidad a los posibles cambios climáticos del cantón Buena Fe, provincia Los Ríos” - Avilés Peñafiel, Milena Julissa (2022)
The research work has a focus on the effects of climate variability on agriculture of changes in crop yields especially corn, in which through a study of agroclimatic zoning allows us to know the most suitable areas or places that the crop has developed efficiently is why we will analyse agroecological zones of corn (Zeas mays) and its adaptability to possible scenarios of climate change in rural areas of Buena Fe canton, province of Los Ríos, using an inductive